Penerapan Metode Belajar Sambil Bermain Dalam Meningkatkan Konsentrasi Belajar Siswa SD - Imelda Oktavia Wibowo; Saifudin Utomo; Cindy Rahma Eka Wulandari; Nela Rofisian (Jurnal Pendidikan Sosial Dan Konseling, 2024)
There are still many students who face difficulties in the learning process because they are not able to divert attention optimally. Good concentration is an important key for learners in understanding the subject matter and a marker of learning success. Various things can have an impact on the level of student concentration while learning, including the atmosphere in the classroom and distractions that can arise from within or outside students during the learning process at school. The purpose of this paper is to describe the strategies, inhibiting factors, educators' efforts in overcoming the lack of concentration of students' learning by using descriptive methods with a qualitative approach obtained data through interviews. The actions taken by educators are to provide guidance to students who like to talk in class, and provide support to students who are less motivated and still feel anxious during the learning process. Educators can also apply the method of learning while playing during learning. Play is a fun and natural learning activity for children, without pressure, and can generate positive interest in children to engage in learning mathematics.